TI_GERICHTE 12.2013.16 vom 21. August 2014 , Donazione - contratto a favore di terzi perfetto - contratto a favore di terzi imperfetto - assegno - TI Tribunale d'appello (2014)
Donazione - contratto a favore di terzi perfetto - contratto a favore di terzi imperfetto - assegno